10.18% PCE of organic solar cells with pyramid micron-structured PDMS. (15th May 2021) - He, Jiaxiong; Zheng, Qiao; Ren, Zhongyang; Yu, Jinling; Deng, Hui; Lai, Yunfeng; Cheng, Shuying
Highlights: A pyramid-shaped micron-structured PDMS film was used in organic solar cells. The size of the pyramid plays an important role of the devices performance. The power conversion efficiency of PTB7-Th: PC71 BM-based cells reaches to 10.18%. The devices with the pyramid-shaped PDMS film presents better stability. Abstract: Since the light harvesting of the organic solar cells (OSCs) is limited by the ultra-thin active layer film due to the low carrier mobility of the organic materials. This study presents a tractable and cost-effective method for enhancement of the light capture of OSCs. A pyramid-shaped micron-structured polydimethylsiloxane (MST-PDMS) anti-reflection film was pasted on the back surface of the OSCs. The MST-PDMS film can reduce the reflectivity of incident light and enhance light capture. Comparing with that of the devices based on the normal indium tin oxide (ITO) glass substrates, the performance of the devices with MST-PDMS was significant improved. The size of the pyramid is an important factor to the performances of the devices. The short circuit current density could increase mostly without sacrificing the open circuit voltage and fill factor, when the width of the pyramid is 9 µm, and a maximum power conversion efficiency (PCE) of PTB7-Th: PC71 BM-based OSCs reaches to 10.18%. Compared with that of the device without the anti-reflection film, PCE was increased by 17.96%. Further, the OSCs with the pyramid-shaped MST-PDMS exhibits a relatively high hydrophobic properties leading to a better stability of the devices at the ambient environment.